PERSEPSI ORANG MUDA KATOLIK TERHADAP REKSA PASTORAL SEBAGAI SARANA PERWUJUDAN IMAN - Adi, Paulus Yosan Kurnia; Wijaya, Albert I Ketut Deni (CREDENDUM: Jurnal Pendidikan Agama, 2024)
This study aims to explore the perceptions of young Catholics towards pastoral care as a means to realize faith. Using quantitative methods, data were collected from 54 respondents in the Santa Maria Parish, Blitar. The results showed that the majority of respondents understood pastoral care as a form of pastoral mission in meeting the needs of the congregation and playing an important role in developing faith. Additionally, the research identified key factors influencing young people's engagement in pastoral activities, including theological understanding, personal experiences, and community support. The findings highlight the significance of adapting pastoral approaches to resonate with the values and expectations of the youth. This study is expected to provide insight for the church in facing modern challenges and increasing the involvement of young people in church life, ultimately fostering a more vibrant and active faith community.